1994
DOI: 10.1902/jop.1994.65.2.139
|View full text |Cite
|
Sign up to set email alerts
|

The Secretion of PGE2, IL‐1β, IL‐6, and TNFα by Adherent Mononuclear Cells From Early Onset Periodontitis Patients

Abstract: The secretion of prostaglandin E2 (PGE2), tumor necrosis factor alpha (TNFα), interleukin 1 beta (IL‐1β), and interleukin 6 (IL‐6) by adherent mononuclear cells (AMNC) from 28 patients with early‐onset periodontitis was studied. The early onset‐periodontitis patients consisted of 12 patients with localized juvenile periodontitis (LJP) and 16 patients with severe generalized periodontitis (SGP). The AMNC responses to different concentrations of lipopolysaccharide (LPS) (E. coli) were determined in these 28 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(119 citation statements)
references
References 35 publications
7
108
0
4
Order By: Relevance
“…Several lines of evidence indicate that the periodontal tissues of LJP patients contain elevated amounts of PGE 2 (9,24,25). Cells of the macrophage/monocyte lineage are a major source of PGE 2 , and a recent study indicates that peripheral blood monocytes from LJP patients produce more PGE 2 than cells from periodontally healthy subjects (30). Therefore, experiments were performed to determine if IgG2 production could be enhanced by PGE 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of evidence indicate that the periodontal tissues of LJP patients contain elevated amounts of PGE 2 (9,24,25). Cells of the macrophage/monocyte lineage are a major source of PGE 2 , and a recent study indicates that peripheral blood monocytes from LJP patients produce more PGE 2 than cells from periodontally healthy subjects (30). Therefore, experiments were performed to determine if IgG2 production could be enhanced by PGE 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the myeloid cells of LJP patients are known to be somewhat abnormal. Among these abnormalities is the production of unusually large amounts of prostaglandin E 2 (PGE 2 ) by both resting and LPS-activated LJP monocytes (30). These observations prompted the hypothesis that PGE 2 could be responsible, at least in part, for the increased IgG2 production that is observed in LJP patients.…”
mentioning
confidence: 99%
“…Even lower concentrations of IL-1I: from LPS-stimulated PB monocytes from periodontitis-susceptible than from periodontitisresistant subjects have been reported (Payne et al, 1993). Further, studies have shown that the PB mononuclear cell IL-la response to oral bacterial strains did not differ among periodontitis categories (Kjeldsen et al, 1995b) and that the endogenous (unstimulated) expression of IL-13 did not differ between periodontitis and clinically healthy subjects (Shapira et al, 1994). These discrepancies, and the apparent individual variation in IL-1 production, may possibly be explained by differences in inclusion criteria for categorizing individuals, numbers of individuals, and variations in disease activity (McFarlane et al, 1990;Gemmell and Seymour, 1993 (Dower et al, 1986a;Mizel et al, 1987), and since most receptor studies have been carried out on T-cells, the following description of the fibroblast IL-I receptor will be supplemented with characteristics of the T-cell receptor.…”
Section: (I) Induction Of Il-i Expression In Fibroblastsmentioning
confidence: 98%
“…Isolation of human peripheral blood monocytes. Fresh monocytes were isolated from the blood of healthy donors by the adherence method (34). Briefly, PBMC were separated from healthy volunteers (Blood bank, Red Cross Transfusion Service, Sydney, New South Wales, Australia) using Ficoll-Hypaque gradients (2).…”
Section: Methodsmentioning
confidence: 99%